Context and Shape: Geographical and Chronological Distribution of Handled Stamp Seals in Anatolia and Northern Levant - Caterina Vignolini (Asia Anteriore Antica)
This article focuses on handled stamp seals, their typological classification, archaeological contexts and geographic distribution. By analyzing a total of 679 seals (302 from good archaeological contexts) over a time period from the Early Bronze Age to the Iron Age, it was possible to point out that specific shapes can be considered typical for the Anatolian region, while others were adopted from Anatolia in the Levant or belong to specific site productions. The data have shown that of the three predominant types (Stalk, Domed and Modelled Domed Knob Seals), probably only one passed from Anatolia to the Northern Levant with a consequent proliferation of variants. All other types of handled stamp seals didn’t provide sufficient data in archaeological contexts to better define the dynamics of production or geographical displacement: therefore, it was only possible to present the general data and propose some hypotheses.